Acyldepsipeptide antibiotics as a potential therapeutic agent against Clostridium difficile recurrent infections. (September 2016) - Gil, Fernando; Paredes-Sabja, Daniel
Alternative antimicrobial therapies based on acyldepsipeptides may hold promising results, based on the fact that they have shown to efficiently eradicate persister cells, stationary cells and cell in biofilm structures of several pathogenic bacteria from the infected host. Clostridium difficile infection is considered the result of extensive hospital use of expanded-spectrum antibiotics, which cause dysbiosis of the intestinal microbiota, enhancing susceptibility to infection and persistence. Considering the urgent need for the development of novel and efficient antimicrobial strategies against C . difficile, we review the potential application to treat C. difficile infections of acyldepsipeptides family of antibiotics, its mechanism of action and current developmental stages.